2015
DOI: 10.4103/0976-237x.166823
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in the pathogenesis of oral submucous fibrosis: A preliminary prospective study

Abstract: Background:In the current scenario pathogenesis of majority of the diseases is deeply linked with the oxidative stress, irrespective of its etiology. Enumerable data suggests that reactive oxygen species play a key role in multistage carcinogenesis. Oral submucous fibrosis (OSMF) is considered as a potentially malignant disorder. Its increased incidence over recent years in the Indian subcontinent is a major health concern to oral physicians. However, the role of oxidative stress has not been widely investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The included studies had found a statistically significant increase in serum MDA levels in OSMF patients compared with controls (p < 0.001). 1,18,20,22,26,28,29,30,31,32,33,34,35,36,37,38 Similarly, other studies also observed a significant difference p-value <0.01 4 and p-value <0.05. 39,40 A few studies have also reported significantly higher salivary MDA levels in OSMF compared with healthy subjects (p < 0.001).…”
Section: Discussionmentioning
confidence: 73%
“…The included studies had found a statistically significant increase in serum MDA levels in OSMF patients compared with controls (p < 0.001). 1,18,20,22,26,28,29,30,31,32,33,34,35,36,37,38 Similarly, other studies also observed a significant difference p-value <0.01 4 and p-value <0.05. 39,40 A few studies have also reported significantly higher salivary MDA levels in OSMF compared with healthy subjects (p < 0.001).…”
Section: Discussionmentioning
confidence: 73%
“…Recent evidences show that the malignant transformation could be caused by the alkaloids of areca nut that are capable of stimulating fibroblasts' growth, the production of cytokines (especially involving the TGF-ÎČ signaling) and immune cells' activation. These mechanisms provoke microenvironment alteration and cellular dysregulation of proliferation, survival, differentiation, DNA repair function and tumor transformation [65,66]. The current therapy options have the aim to reduce symptoms and to improve the patients' quality of life.…”
Section: Oral Submucous Fibrosis (Osf)mentioning
confidence: 99%
“…Arecoline stimulates the fibroblast cells to express growth factors and cytokines that enhance the collagen deposition and repress the collagen degradation. Clinical studies reported transforming growth factor beta (TGF-ÎČ), connective tissue growth factor (CTGF), beta fibroblast growth factor (bFGF) [ 104 ], alpha-smooth muscle actin (α-SMA) [ 105 ], tumor necrosis factor-α (TNF-α) [ 106 ], serum c-reactive protein [ 107 ], ROS level [ 108 ], matrix metalloproteinases (MMP), and the tissue inhibitors of metalloproteinases (TIMP) [ 109 ] were expressed abnormally in OSF group.…”
Section: The Mechanism Of Osf Pathogenesis and Malignant Transformmentioning
confidence: 99%
“…However, this mechanism is disrupted in OSF. Arecoline also increases the ROS level in OSF patients’ serum [ 108 ]. Serum ROS attacks the structure of the blood vessels in endothelial cells, induced cell senescence [ 113 ], and DNA double-stranded breaks [ 114 ].…”
Section: The Mechanism Of Osf Pathogenesis and Malignant Transformmentioning
confidence: 99%